Potencial produtivo da cana-de-açúcar sob irrigação por gotejamento em função de variedades e ciclos - Silva, Marcelo De A. [UNESP]; Arantes, Marcel T. [UNESP]; Rhein, Andressa F. De L. [UNESP]; Gava, Glauber J. C.; Kolln, Oriel T. (Departamento de Engenharia Agrícola - UFCG, 2014)
This study aimed to evaluate the yield potential of different varieties of sugarcane under drip irrigation in two growth cycles. A trial was set up in October 2006 at Jaú region (São Paulo state, Brazil), in an experimental field with a eutrophic Ultisol. The experiment was conducted in randomized complete blocks with factorial treatment structure 8 x 2, constituted by eight sugarcane varieties and two crop cycles, with six replicates. Stalk productivity (TCH), sugar productivity (TPH), juice quality traits and water use efficiency in relation to stalk productivity were evaluated in each crop cycle. It was observed that varieties of sugarcane respond differently to full irrigation, and this response is influenced by climatic conditions of the agricultural year. In this study, only the first evaluation cycle (plant cane) was decisive to differentiate the performance among the varieties. The varieties IAC91-1099, IACSP96-3060, RB855536, RB867515 and SP85-1115 showed higher agro-industrial yield potential and less consumption of water and can be recommended for the management of production under drip irrigation.

Este trabalho foi realizado com o objetivo de avaliar o potencial produtivo de diferentes variedades de cana-de-açúcar irrigadas plenamente por gotejamento durante dois ciclos. O experimento foi instalado na região de Jaú, SP, em um Latossolo Vermelho eutrófico. O delineamento experimental foi o de blocos casualizados em arranjo fatorial 8 x 2 (variedades x ciclos), com seis repetições. Em cada ciclo foram avaliadas variáveis de qualidade do caldo, produtividade de açúcar e de colmos e eficiência de utilização de água em relação à produtividade de colmos. Observou-se que variedades de cana-de-açúcar respondem diferentemente à irrigação plena, sendo esta resposta influenciada pelas condições climáticas do ano agrícola. Nesta pesquisa apenas o primeiro ciclo de avaliação (cana-planta) foi determinante para diferenciar o desempenho entre as variedades. As variedades IAC91-1099, IACSP96-3060, RB855536, RB867515 e SP85-1115 apresentaram melhor potencial produtivo agroindustrial e menor consumo relativo de água podendo, então, ser recomendadas para o manejo de produção com irrigação por gotejamento.
Yield potential of sugarcane under drip irrigation in function of varieties and crop cycles
Keywords: Saccharum spp.; eficiência do uso da água; produtividade; cultivares; pol% cana; Saccharum spp.; water use efficiency; productivity; cultivars; pol% cane